Penerapan Mental Accounting dalam Pengelolaan Keuangan Pribadi Mahasiswa Generasi Zelenial - Candrakusuma, Desy Amalia; Dewinda, Mutty Claudia (JURNAL ILMIAH EDUNOMIKA, 2024)
Every individual definitely needs money to fulfil various types of needs, so it is necessary to do financial management properly. The purpose of this research is to find out how the application of mental accounting to Gen Z's personal financial management. This research was conducted at the Accounting Study Programme, Surakarta University with 5 students who are Gen Z people. This research uses a qualitative descriptive method. The results of this study indicate that each respondent has different mental accounting, so that each respondent has the ability to do financial management differently. This research is expected to contribute to financial literacy, especially for Gen Z.